Generation Z Entrepreneurial Morals towards Intention through Self-Efficacy and Motivation, Based on Creative Economy - Ningsih, Caria; Nauval, Muhammad Luthfi; Turgarini, Dewi (Jurnal Moral Kemasyarakatan, 2024)
This research aims to identify the influence of entrepreneurial morals on entrepreneurial intention, with self-efficacy and entrepreneurial motivation as intervening variables among Generation Z students of tourism study program. This is a quantitative research using the Path Analysis method. Based on computation, sample of this research is using 100 tourism students from Indonesian Education University (UPI), who are participating in the entrepreneurship program. The results of the study indicate that entrepreneurial motivation plays an important role as a significant mediator in linking entrepreneurial moral with entrepreneurial intention, while self-efficacy does not have a significant influence on the relationship between entrepreneurial moral to entrepreneurial intention. Overall, entrepreneurial moral play a significantly important role in increasing the self-efficacy, entrepreneurial motivation and entrepreneurial intention of tourism students. It is expected that this research can recommend and contribute to the development of a more effective and relevant creative economy-based entrepreneurship program to increase interest in entrepreneurship among tourism students.